Tissue reaction to Aroeira (Myracrodruon urundeuva) extracts associated with microorganisms: an in vivo study - Carlos Roberto Emerenciano Bueno; Diego Valentim; Élerson Gaetti Jardim Junior; Daniela Nardi Mancuso; Gustavo Sivieri-Araujo; Rogerio Castilho Jacinto; Luciano Tavares Angelo Cintra; Eloi Dezan-Junior (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract: Based on aroeira's (Myracrodruon urundeuva) antimicrobial activity and a future trend to compose intracanal medication, the aim of this study was to assess in vivo inflamatory tissue response to the extracts by edemogenic and histological analysis containing inactivated facultative and anaerobic microorganisms. For edema quantification, eighteen animals were divided into three groups (n = 3, periods: 3 and 6 hours) and 0.2 mL of 1% Evans blue per 100 g of body weight was injected into the penile vein under general anesthesia. After 30 min the animals received a subcutaneous injection in the dorsal region of aqueous or ethanolic extract of aroeira or saline (control) containing inactivated bacteria. Samples were collected, immersed in formamide for 72h, and evaluated by spectrophotometry (630 m). For histological analysis, polyethylene tubes with the extracts were implanted in the dorsal of 30 male rats. Analysis of the fibrous capsule and inflammatory infiltrate were performed after 7 and 30 days. The aqueous extract group induced less edema in both postoperative periods compared to the other groups, but the differences were not significant (p > 0.05). Tissue repair was significantly better after 30 days than after 7 days (p < 0.01). The aqueous solution showed less inflammatory response than the ethanolic solution (p < 0.05), with tendency for better results than control after 7 days. After 30 days, the response to both extracts was similar to control. The aqueous and ethanolic aroeira extracts containing inactivated microorganisms showed a trend for better results than saline, even when associated with microorganisms, and facilitated the tissue repair process.